Achieving Organizational Objectives through Satisfying Customer's Expectations in the Polythene Industry with Special Reference to Lanka Polythene Industry Company - Shanmugam, S. (A thesis submitted for the Master of the Business Administration Degree, 2012)
The saying goes "the customer is always right" and the "customer is King". But, is it really practiced in Sri Lanka? Customer service is perhaps the most powerful diamention in the marketing mix of any company or industry. In one sense the development of targeted customer service strategies is only the logical extension of- the marketing concept. In other words customer service is about recognizing the specific needs and expectations of the customers and developing a strategy that focuses the resources of the organization towards meeting those needs and expectations. …